Pathology of fatal diffuse brain injury in severe non-penetrating head trauma - Kodchakan Rungruangsak (2022)
Traumatic brain injury (TBI) is recognised as a serious global public health problem that imposes a heavy socioeconomic burden on society. The vast majority of cases result from road traffic accidents and falls, and the injuries are mainly attributed to velocity-related mechanisms. Lethal cases are mostly found to suffer from severe diffuse brain injuries (DBI), comprising diffuse vascular injury, diffuse axonal injury (DAI), generalized cerebral edema and ischemic-hypoxic injury. Coup and contrecoup brain contusions may also occur. This study set out to describe the pathological findings of severe DBI in terms of survival times and Abbreviated Injury Scale (AIS) severity scores. The autopsy data from 2 recent years (2018 and 2019) were reviewed to recruit over 800 cases presenting with severe head injuries. Many demographic characteristics of TBI were identified (for example, causes, victim genders and victim ages). These were revealed to be like those previously reported in the literature, confirming that there are shared risk factors across the globe. The hallmarks of severe TBI—such as a unimodal survival distribution and a period for detecting DAI via conventional staining—were also evident, as per previous reports. However, it was noticed that the histopathological detection rates of DAI surged after 72 h, which might be because these injuries are mediated by secondary axotomy. This study also analysed real brain weights to identify the time period for the development of cerebral edema in humans; this period seems to have never been reported. The increment time of cerebral edema reached a peak in 12 h, after which the condition sustained for at least 72 h. This may be a golden period in clinical practice as well as a prognostic factor in forensic medicine.